Diagnóstico da estrutura da paisagem da estação ecológica de Avaré e seu entorno, como subsídio à sua conservação - Galetti, Gabriela (Universidade Federal de São Carlos, 2013)
The process of agricultural expansion caused an increase in forest fragmentation and, consequently, it was responsible for the conversion of the forest into a mosaic with different land-cover patches and remnants of the original forest. In order to identify the distribution of the remnants in a 3 km-radius around the Estação Ecológica de Avaré - EEA, we produced a land-use/land-cover map of this landscape. Based in this map it was calculated the landscape metrics. The natural vegetation occupied 21.2% of the area and it was distributed in 59 patches in an agricultural matrix. The largest remnant has 587.68 ha. According the landscape metrics only 6,7% of the natural vegetation are larger than 50 ha and, consequently 93% of this remnants are small. The shapes of the forest remnants are predominantly irregular and lengthened because it was close to surface water and, consequently, in a buffer zone of the Permanent Preservation Areas (PPA), which occupied 6.3% of total landscape (65% cover by natural vegetation). The man intervention was responsible for the conversion of the 35% of the PPA area into a mosaic with different land-cover, in this case, with agriculture and urban occupation. Consider the flux of the sub-tribe Euglossina bees, the EEA is not isolated and permitted a forest connection. The forest remnants, although, suffer with the negative pressure done by the agriculture. In this context, we concluded that the landscape metrics permit the evaluation of the landscape context and facilitate the definition of action aim at the forest and landscape conservation.
Keywords: Área de Preservação Permanente (APP); Biodiversidade - conservação; Vegetação - mapeamento; Métricas da paisagem; Vegetação natural; Biodiversity conservation; Landscape metrics; Natural vegetation; CIENCIAS AGRARIAS::RECURSOS FLORESTAIS E ENGENHARIA FLORESTAL::CONSERVACAO DA NATUREZA